MANAJEMEN RISIKO PADA PROYEK GEDUNG BERTINGKAT DI BANJARMASIN - Candra Yuliana; Gawit Hidayat (INFO-TEKNIK, 2017)
Process of implementation of the high building construction usually takes a long time and complex so it can cause uncertainty and various risks. The purpose of the research are analysis of the significant risks and determine the response to significant risks.The research process is performed by survey. Data questionnaire analysis begins with risk identification through the study of literature, after it carried out a risk analysis conducted by distributing questionnaires to a number of respondents. Respondents are site manager, site engineer, logistics mechanics, team leader, supervising consultants. The risk analysis is done by estimating the likelihood that the biggest risk will occur and the resulting impact on costs and step time ast conduct risk response by way of interviews with selected respondents. Assessment of the risk by Severity Index and Probability Impact Grid. Based on the analysis found that the variable is a significant risk with respect to time, there are six kinds of risks as well as the response variable. While variable significant risks to cost, there are five kinds as well as its.